A bibliometric analysis of Oropouche virus - Dong, Jingsha; Li, Zichen; Gao, Shan; Zhang, Leiliang (Frontiers in Microbiology, 2024)
Objectives: Oropouche virus (OROV) causes systemic infections including the nervous and blood systems, posing a significant and growing public health challenge. However, a comprehensive review of the bibliometric analysis of OROV is still lacking. Therefore, the objective of this study was to provide insight into the research dynamics and current hotspots of OROV. Methods: This study used bibliometric analysis to explore the current status of research related to OROV. 148 publications from 1961 to 2024 were retrieved from the Scopus database. Countries, authors, institutions, journals, references, and keywords were visualized using VOSviewer, CiteSpace, R studio, and Bibliometrix. Microsoft Excel was used for statistical analysis. Results: Brazil is the country with the highest number of publications, total cited frequency, and the most extensive international collaboration. The most popular journal in this field is the American Journal of Tropical Medicine and Hygiene. Instituto Evandro Chagas is the institution with the highest number of publications, and Eurico Arruda is involved in the highest number of publications. Keyword co-occurrence analysis showed that Oropouche bunyavirus, virology, bunyavirus, priority journal, and nucleotide sequence are the main research hotspots in this field. Conclusion: Our study provides a comprehensive overview of the research trends and key areas of focus in OROV. The field is currently experiencing rapid growth, as evidenced by the rising number of annual publications, which not only highlights increased research activity but also lays a solid foundation for further in-depth investigations. This trend offers valuable insights for developing effective strategies for outbreak prevention and control in public health. Presently, researchers are concentrating on the detailed study of Bunyavirus infections, employing both virological and genetic approaches to elucidate their complex pathogenic mechanisms.